Variasi Genetik dan Filogeografi Pisang Raja (Musa spp.) di Pulau Jawa Berdasarkan Sekuen Internal Transcribed Spacer - Wahyudi, Didik; Gusmiati, Lutfiana Hasanah; Hapsari, Lia (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2023)
Pisang Raja is an important banana cultivar for the Javanese people since ancient times, with many morphological variations and local names. This study aims to determine the genetic variation and phylogeography of Pisang Raja based on Internal Transcribed Spacer (ITS) sequences. The results of the research can be used as a reference for developing superior Pisang Raja cultivars that are resistant to disease and make farmers easier to choose Pisang Raja cultivars that suit with geographical conditions on Java Island. This study used 9 samples of Pisang Raja (in-group) and 2 samples of wild bananas (out-group). The research method started with DNA isolation, qualitative and quantitative tests, ITSL and ITS4 primer amplification, and sequencing. Data analysis performed included polymorphism, phylogenetics (MP, ML, NJ and BI) and haplotype. The results showed that the ITS sequences in Pisang Raja was amplified with a length of 600-700 bp and GC content of 61.70%. Polymorphism analysis showed that the genetic variation of Pisang Raja in Java was very high. Phylogenetic analysis resulted in 4 phylogenetic trees with relatively same topologies, where the in-groups were divided into 2 clades, namely clade I (AAA and AAB) and clade II (AAA and ABB). The highest genetic similarity was showed by Raja Brentel and Raja Bali (89.43%) and the least was Raja Gareng and Raja Seribu (56.82%). Haplotype analysis formed 11 haplotypes which grouped into 4 groups. Pisang Raja evolution comes from two ancestors, i.e. M. acuminata and M. balbisiana. The phylogeography of ITS gene flow in Pisang Raja originates from Central Java then spread to East Java and Jakarta. This is presumably due to the high utilization followed by the planting of Pisang Raja by the people of Central Java for ritual and ceremonial events in the past which influenced the domestication process. The results of this study can served as the reference for genetic conservation strategy of Pisang Raja.